Time-resolved pulsed OSL of ceramic YAP:Mn phosphors. Issue 196 (12th February 2019) - Afanassyev, D.; Ubizskii, S.; Zhydachevskyy, Ya.; Luchechko, A.; Popov, A. I.; Suchocki, A.
Abstract: The paper deals with the results of comparative study on time-resolved pulsed optically stimulated luminescence (TR-OSL) response of ceramic YAP:Mn materials prepared by different methods. In particular, the ceramics prepared from the nanocrystalline material synthesized by the solution combustion method and ones obtained by the solid-state synthesis have been studied comparatively. These studies have revealed that the TR-OSL decay of both materials features a non-exponential behavior. The Becquerel decay function with three parameters fits quite well their decay responses recorded over wide time scale and dynamic range. The mean relaxation time estimated from fitting parameters differs significantly for samples fabricated by different technologies. This difference between two types of ceramics is discussed in the framework of the trap structure of the materials.